Helminth Antigens Enable CpG-Activated Dendritic Cells to Inhibit the Symptoms of Collagen-induced Arthritis through Foxp3+ Regulatory T Cells - Carranza, Franco Alfredo (2012)
Dendritic cells (DC) have the potential to control the outcome of autoimmunity by modulating the immune response. In this study, we tested the ability of Fasciola hepatica total extract (TE) to induce tolerogenic properties in CpG-ODN (CpG) maturated DC, to then evaluate the therapeutic potential of these cells to diminish the inflammatory response in collagen induced arthritis (CIA). DBA/1J mice were injected with TE plus CpG treated DC (T/C-DC) pulsed with bovine collagen II (CII) between two immunizations with CII and clinical scores CIA were determined. The levels of CII-specific IgG2 and IgG1 in sera, the histological analyses in the joints, the cytokine profile in the draining lymph node (DLN) cells and in the joints, and the number, and functionality of CD4+CD25+Foxp3+ T cells (Treg) were evaluated. Vaccination of mice with CII pulsed T/CDC diminished the severity and incidence of CIA symptoms and the production of the inflammatory cytokine, while induced the production of anti-inflammatory cytokines. The therapeutic effect was mediated by Treg cells, since the adoptive transfer of CD4+CD25+ T cells, inhibited the inflammatory symptoms in CIA. The in vitro blockage of TGF-b in cultures of DLN cells plus CII pulsed T/C-DC inhibited the expansion of Treg cells. Vaccination with CII pulsed T/C-DC seems to be a very efficient approach to diminish exacerbated immune response in CIA, by inducing the development of Treg cells, and it is therefore an interesting candidate for a cell-based therapy for rheumatoid arthritis (RA).Fasciola hepatica total extract (TE) to induce tolerogenic properties in CpG-ODN (CpG) maturated DC, to then evaluate the therapeutic potential of these cells to diminish the inflammatory response in collagen induced arthritis (CIA). DBA/1J mice were injected with TE plus CpG treated DC (T/C-DC) pulsed with bovine collagen II (CII) between two immunizations with CII and clinical scores CIA were determined. The levels of CII-specific IgG2 and IgG1 in sera, the histological analyses in the joints, the cytokine profile in the draining lymph node (DLN) cells and in the joints, and the number, and functionality of CD4+CD25+Foxp3+ T cells (Treg) were evaluated. Vaccination of mice with CII pulsed T/CDC diminished the severity and incidence of CIA symptoms and the production of the inflammatory cytokine, while induced the production of anti-inflammatory cytokines. The therapeutic effect was mediated by Treg cells, since the adoptive transfer of CD4+CD25+ T cells, inhibited the inflammatory symptoms in CIA. The in vitro blockage of TGF-b in cultures of DLN cells plus CII pulsed T/C-DC inhibited the expansion of Treg cells. Vaccination with CII pulsed T/C-DC seems to be a very efficient approach to diminish exacerbated immune response in CIA, by inducing the development of Treg cells, and it is therefore an interesting candidate for a cell-based therapy for rheumatoid arthritis (RA).+CD25+Foxp3+ T cells (Treg) were evaluated. Vaccination of mice with CII pulsed T/CDC diminished the severity and incidence of CIA symptoms and the production of the inflammatory cytokine, while induced the production of anti-inflammatory cytokines. The therapeutic effect was mediated by Treg cells, since the adoptive transfer of CD4+CD25+ T cells, inhibited the inflammatory symptoms in CIA. The in vitro blockage of TGF-b in cultures of DLN cells plus CII pulsed T/C-DC inhibited the expansion of Treg cells. Vaccination with CII pulsed T/C-DC seems to be a very efficient approach to diminish exacerbated immune response in CIA, by inducing the development of Treg cells, and it is therefore an interesting candidate for a cell-based therapy for rheumatoid arthritis (RA).+CD25+ T cells, inhibited the inflammatory symptoms in CIA. The in vitro blockage of TGF-b in cultures of DLN cells plus CII pulsed T/C-DC inhibited the expansion of Treg cells. Vaccination with CII pulsed T/C-DC seems to be a very efficient approach to diminish exacerbated immune response in CIA, by inducing the development of Treg cells, and it is therefore an interesting candidate for a cell-based therapy for rheumatoid arthritis (RA).